A 5–bit CMOS attenuator with low temperature and process variations for Ka‐band phased‐array applications. Issue 9 (8th June 2021) - Lei, Xin; Ye, Liqun; Li, Shengjun; Deng, Chun; Fan, Chao; Gui, Xiaoyan; Yan, Binyu; Liu, Changjun
Abstract: A 5‐bit CMOS attenuator with low temperature and process variations is presented employing the proposed optimization and compensation technique to achieve low root mean square (RMS) attenuation error and phase variation. The proposed design technique includes optimizing ratio of transistors and attenuation resistors to reduce the temperature and process variations, and utilizing a temperature and process compensation circuitry to further minimize the chip‐to‐chip and channel‐to‐channel variations. The presented attenuator is fabricated in a 55 nm CMOS process and achieves a maximum attenuation of 15.5 dB with 0.5 dB‐per‐step resolution. Measurement results show that the maximum RMS attenuation error is 0.6 dB and phase variation is less than ±2.2°, from −45 to 85°C and between different chips or channels within frequency range from 25 to 32 GHz. The core area is 0.32 × 0.5 mm 2 excluding pads.